Ações avaliativas docentes em anos finais do ensino fundamental e construção coletiva de uma formação para a melhoria das práticas - Forti, Maria Cristina (2021)
This research proposes elements for the analysis of the evaluation practices carried out by a group of teachers from the final years of elementary school at a private teaching unit in the city of São Paulo, with a view to the collective construction of a training proposal for the improvement of selected learning assessment actions. Adjacent to this analysis, the study advocates continuing teacher education to improve formative assessment. Authors cited in the theoretical framework are Hadji (2001), Fernandes (2008 and 2009), Black et al (2004), Depresbiteris and Tavares (2009), contributed to the understanding of the pedagogical uses of assessment for learning in the classroom, in the development of pedagogical practice, in light of the design of formative assessment. Authors such as Moriconi et al (2017), Passos (2016), André (2017), Lüdke and André (2018), contributed to the understanding of the characteristics of an effective teacher education, which is leveraged by collective and collaborative actions, among trainers and teachers, within the school. As a general objective, investigation of the evaluative strategies of a group of teachers in the development of student learning and collectively and collaboratively build training for the improvement of the teachers' assessment practices was sought To carry out the study, the methodology of action research and inspiration in the assumptions of Bardin (2016) were used for content analysis. In this sense, a semi-structured interview was carried out with each professor and two meetings with the group formed by the five professors and the researcher, which were recorded. These records were complemented by a logbook written by the researcher during the meetings. The results presented make it possible to believe that teachers, in their discourse and practices, seem to understand the concept of formative assessment; however, professors lack greater rationalization of these processes; the professors value the training processes and understand that the assessment of learning should be further explored in continuing education, as well as the methodologies used should favor the exchange of experiences and collaborative movements between them. Finally, in light of formative assessment and the characteristics that indicate the effectiveness of teacher training, a training proposal was collectively elaborated, with a commitment to its realization